HBV Reactivation During the Treatment of Non-Hodgkin Lymphoma and Management Strategies - Cao, Xing; Wang, Yafei; Li, Panyun; Huang, Wei; Lu, Xiaojuan; Lu, Hongda (Frontiers in Oncology, 2021)
Hepatitis B virus reactivation (HBV-R) is now a common and well-known complication during the treatment of Non-Hodgkin lymphomas (NHL) patients with current or past exposure to hepatitis B virus infection which can lead to significant morbidity and mortality. HBV-R is deemed to be closely associated with chemotherapeutic or immunosuppressive therapies, whereas immunosuppressive agents such as anti-CD20 antibody therapy (eg, rituximab), glucocorticoids and hematopoietic stem cell transplantation (HSCT) therapy are administered to NHL patients during the treatment that can cause deep immunodepression usually put them at high risk of HBV-R. In this review, we explored current evidences and several national and international guidelines and expert panels’ recommendations about the definition, risk factors, screening and monitoring strategies, choice of antiviral therapies between prophylaxis and pre-emptive therapy as well as the optimal antiviral agent and duration of antiviral therapy for HBV-R. We hope to provide a wider horizon for doctors engaged in the treatment of patients with NHL about HBV-R and the appropriate management strategies.